The end of race? : Obama, 2008, and racial politics in America - Kinder, Donald R. (JSTOR EBA., 2012)
This book examines the role of racism in the 2008 Presidential election. How did race affect the election that gave America its first African American president? This book offers some fascinating, and perhaps controversial, findings. The authors assert that racism was in fact an important factor in 2008, and that if not for racism, Barack Obama would have won in a landslide. On the way to this conclusion, they make several other important arguments. In an analysis of the nomination battle between Obama and Hillary Clinton, they show why racial identity matters more in electoral politics than gender identity. Comparing the 2008 election with that of 1960, they find that religion played much the same role in the earlier campaign that race played in 2008. And they argue that racial resentment, a modern form of racism that has superseded the old-fashioned biological variety, is a potent political force.